Formulation development and evaluation of duloxetine extended-release tablets (World Journal of Current Medical and Pharmaceutical Research, 2021)
Duloxetine  is an anti-depressant drug which is used in depression. The aim of present investigation was to prepare an ER tablet of duloxetine with similar dissolution profile matching to Effexor ER. An immediate release core tablet of 100mg was prepared and it was compression coated using HPMC matrix system. HPMC of three viscosity grades i.e., K4M, K15M, K100M and different concentrations of 15% polymer, 25% polymer, 35% polymer & 45% polymer were taken. With the above polymers by using wet granulation and direct compression process 11 formulations were prepared. The data obtained from in vitro drug release was used to determine the similarity factor between marketed and optimized product. Out of all F11 formulation (K15M 35% polymer) is optimized and is matching with the marketed product.